KUALITAS LAYANAN PERGURUAN TINGGI YANG BERPENGARUH TERHADAP KEPUASAN MAHASISWA DAN KONSEKUENSI PERILAKU MAHASISWA - Imam nuraryo (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2016)
The purpose of this paper is to analyze the influence of perceived service quality, perceived value, image on student satisfaction, and determine the consequences of student satisfaction in one private Bandung University (Prima University). In order to accomplish the objectives proposed, a model reflecting the influence of perceived service quality, perceived value, image on student satisfaction, and reflecting the relationship bet ween satisfaction and behavioral consequences, the model is tested by structural equations and the final sample is 280 students. The findings show that image has a positive effect on student satisfaction, and the satisfaction has a positive effect on student loyalty ,and negative effect on student complaint, if higher education institutions have to compete through student satisfaction, It is proven by this paper that the construct which most influences student satisfaction in higher education is the image construct ,also it is proven that if the student satisfaction rises, the loyalty will increase and complaint will decrease.